Музыка в романе Евгения Водолазкина Брисбен - Kopac, Tatiana (Studia Rossica Posnaniensia, 2023)
The author of the article examines the role of music in Evgeny Vodolazkin’s novel Brisbane, analyzing individual manifestations of the widely understood intermediacy. The musical code of the text is expressed in audibility of the sounds the world of the novel is filled with, and in musical ecphrasis (the profession of the protagonist, professional vocabulary and slang, references to musical compositions; descriptions of the world of music through the prism of the characters’ perception). These techniques perform plot and semantic functions, combine two equal plot plans, and constitute the image of the protagonist and other important characters. Fragments with musical ecphrasis have a vivid narrative, emotionally saturated (“moments of explosion”). The main emotional codes (or affects) find expression in the selection of musical compositions that assert the dramatic direction of the narrative. Music in the novel expresses the hero’s inner state, his relationship to the world, and symbolizes the metaphysical breakthrough experienced by the hero: from love and sound, to silence and eternity.